A Bibliometric Comparative Study of Servant and Instructional Leadership and Their Influence on Teacher Motivation in Public and Private Schools - Lapore, Dennis Jr. S.; Sandoval, Mhara S.; Santos, Joseline M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study addresses the growing interest in how leadership styles affect teacher motivation, a critical factor in improving educational quality. Leadership plays a central role in shaping school culture, teacher engagement, and instructional outcomes. Among the many approaches, servant leadership and instructional leadership have gained prominence due to their focus on teacher well-being and performance. However, a comprehensive comparison of these styles in different school settings remains limited. To explore this gap, the study analyzed 99 peer-reviewed documents indexed in a major academic database from 1993 to 2025. A bibliometric method was used to map key trends, influential authors, and major themes. Visual and quantitative tools were applied to identify connections among publications and topics related to leadership and motivation. The results show that both servant and instructional leadership positively influence teacher motivation, though they operate through different mechanisms. Instructional leadership focuses on academic goals and teaching strategies, while servant leadership emphasizes trust, empathy, and support. Cultural and institutional contexts influence the effectiveness of each style. The study concludes that combining relational and instructional leadership elements can enhance teacher motivation, especially when adapted to specific school environments. These findings offer practical guidance for school leaders and policymakers aiming to improve teacher satisfaction and performance. The study also contributes to the global goal of promoting inclusive and high-quality education by highlighting leadership as a key driver of teacher motivation in both public and private schools.